Sex preference in urban Nepal - Adhikari, N.; Ghimire, A.; Ansari, I (Journal of Institute of Medicine Nepal, 2008)
Introduction: Altered sex ratio at birth is strong indicator of bias against unwanted sex. Sex selection is currently possible through advanced technology of pre implantation sex selection, prenatal sex diagnosis and sex selective abortions. In Nepal, though preference for sons is strong, there is no evidence of altered sex ratio at birth on country wide basis.Methods: This retrospective study was done at Patan Hospital, Kathmandu, Nepal. All live born babies born during a period of five years (2003 to 2007) were divided into three groups-first live born babies, second live born babies and the rest grouped as third and subsequent live born babies. Their sex was recorded and results were analyzed.Results: Over the entire study period, 114 boys were born for every 100 girls (normal being 102 to 106 boys for every 100 girls). For the first live births, the ratio was 106 boys to 100 girls. For the second live birth, it was 118 to 100. For third and successive births this ratio was 177 to 100.Conclusion: There was a highly significant decrease in proportion of female births for third and successive births. Over the years, there is some decrease in proportion of female births in all three groups. However, it is statistically not significant that there is a practice of sex selective abortions in practice in Kathmandu.